Ethnopedological knowledge by local farmers in Sarawak for agricultural activity : a case study at Nanga Machan, Kanowit - Alissee Sherrylin, anak Bagol (Universiti Malaysia Sarawak (UNIMAS), 2012)
Ethnopedology is one aspect of indigenous knowledge, which study on the local people knowledge in evaluating the soil fertility and suitability for agriculture purposes while encompassed of soil and land use knowledge systems of rural populations. Sarawak, Malaysia is a largest state that consists of various kinds of indigenous groups such as Iban, Chinese, Malay, Bidayuh, Melanau and the Orang Ulu. From this study, five types of soils sample referred by farmers found to contain high level of acidity locally known Tanah hitam, Tanah pasir, Tanah kuning, Tanah batu lemak and Tanah ladu. Tanah hitam (Black soil) which farmers ranked is the highest preference among other soils referred. Ranking for soil fertility from most fertile to less fertile is Tanah hitam, Tanah kuning, followed by Tanah batu lemak, next is Tanah pasir and lastly Tanah ladu. Information gained from this study can be use by researcher and other relevant party to assist farmer in improving soil fertility and agriculture practices or as a guideline for future soil use practices.